The multicultural riddle : rethinking national, ethnic, and religious identities - Baumann, Gerd. (Zones of religion, 1999)
"A Riddle is a paradox that can be solved by rethinking the terms in which it is posed. Multiculturalism, too, is a riddle. It asks how we can establish a state of justice and equality between and among three parties: those who believe in a unified national culture, those who trace their culture to their ethnic identity, and those who view their religion as culture. To solve the riddle, one needs to rethink what is meant by nationality or the nation-state, by ethnic identity or ethnicity, and by religion as a basis of culture. What all three acts of rethinking have in common is a new concern with the meaning and making of culture. Multiculturalism is not the old concept of culture multiplied by the number of groups that exist, but a new, and internally plural, praxis of culture applied to oneself and to others. This is what this book tries to show."--BOOK JACKET.